Ḫatti and Ḫattuša - Kryszeń, Adam (Altorientalische Forschungen, 2017)
The article addresses long-standing but still pertinent questions regarding the two most frequent toponyms in Hittite texts: Ḫatti and Ḫattuša . The first question concerns the exact meaning of each name. Was Ḫatti the Akkadian name for Ḫattuša , as is widely (although not universally) held, or are both originally Hittite names? If the former view is adopted, then subsequent questions naturally arise, namely: What is the origin of the name Ḫatti ? And how did it come to be used by the Hittites? In order to deal with these issues, all attestations of both toponyms have been collected and analyzed statistically, taking various criteria into consideration: the dating and language of the texts mentioning Ḫatti and Ḫattuša , the determinatives, and the immediate context of the attestations.